2014
DOI: 10.1016/j.devcel.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The CDC42-Interacting Protein 4 Controls Epithelial Cell Cohesion and Tumor Dissemination

Abstract: The role of endocytic proteins and the molecular mechanisms underlying epithelial cell cohesion and tumor dissemination are not well understood. Here, we report that the endocytic F-BAR-containing CDC42-interacting protein 4 (CIP4) is required for ERBB2- and TGF-β1-induced cell scattering, breast cancer (BC) cell motility and invasion into 3D matrices, and conversion from ductal breast carcinoma in situ to invasive carcinoma in mouse xenograft models. CIP4 promotes the formation of an E-cadherin-CIP4-SRC compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 50 publications
5
47
0
Order By: Relevance
“…In fact, CIP4 promotes lamellipodia formation in cortical neurons (Saengsawang et al, 2012) and localizes at the leading edge in tumor cells (Pichot et al, 2010;Truesdell et al, 2014). A recent study has shown that CIP4 regulates cell cohesion by modulating E-cadherin endocytosis and the actomyosin contraction required to break cell-cell junctions, thus facilitating cell migration (Rolland et al, 2014). Therefore, previous studies support the hypothesis that CIP4 participates in cell migration through its canonical role in integrating membrane deformation and actin dynamics.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In fact, CIP4 promotes lamellipodia formation in cortical neurons (Saengsawang et al, 2012) and localizes at the leading edge in tumor cells (Pichot et al, 2010;Truesdell et al, 2014). A recent study has shown that CIP4 regulates cell cohesion by modulating E-cadherin endocytosis and the actomyosin contraction required to break cell-cell junctions, thus facilitating cell migration (Rolland et al, 2014). Therefore, previous studies support the hypothesis that CIP4 participates in cell migration through its canonical role in integrating membrane deformation and actin dynamics.…”
Section: Discussionsupporting
confidence: 69%
“…6C). Considering that CIP4 is involved in several processes related to cell migration, including the disassembly of the adherens junctions (Rolland et al, 2014), the mechanism involved in centrosome and Golgi polarization could be independent of the interaction of CIP4 with AKAP350. Therefore, we evaluated whether this interaction was relevant for centrosomal and Golgi polarization.…”
Section: Akap350 Recruits Cip4 To the Centrosome In Migrating Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…CIP4 is an effector of Cdc42, another Rho-like GTPase critical to actin dynamics, migration, and endocytosis that is also frequently altered in cancer. CIP4 overexpression in breast cancer represents an independent predictor of disease outcome, being associated with poorer prognosis and metastasis (15,16). Mechanistically, this is due to increased E-cadherin internalization leading to cell scattering and improved actomyosin contractility (16).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, HEK cells grown on elastic substrates into embryonic bodies exhibited higher actin tension than on glass, so did TGFb1-treated, hRas-transformed MDCK cells [27]. In mammary epithelial cells, epithelial growth factor (EGF) increased E-cadherin tension, presumably through a CIP4-dependent control of actomyosin contraction [47].…”
Section: Sensitivity To Extracellular Cuesmentioning
confidence: 96%